A template method to measure the t(t)over-bar polarisation - Aguilar-Saavedra, J. A. (2022)
This manuscript has no associated data or the data will not be deposited. [Authors’ comment: The datasets generated during and/or analysed during the current study are available from the corresponding author on reasonable request.]